Bioenergetic signatures of circulating blood cells as biosensors of metabolic health in food-producing animals - Ipharraguerre, Ignacio R.; Rosales Cavaglieri, Lorenzo A.; Rimbach, Gerald (Frontiers in Veterinary Science, 2025)
The intensification of animal production has substantially increased productivity, yet it has concurrently increased the metabolic vulnerability of livestock and poultry. Traditional biomarkers often lack sensitivity and fail to capture early or systemic dysfunction. In recent years, the bioenergetic profiling of circulating blood cells, particularly peripheral blood mononuclear cells and platelets, has emerged as a minimally invasive tool to assess mitochondrial function and systemic metabolic health. This critical review explores the application of blood-based bioenergetic assessments in food-producing animals, drawing parallels from human clinical research where such approaches have contributed to describe metabolic, inflammatory, and immune-related disorders. We highlight how respirometry and extracellular flux analysis enable high-resolution characterization of cellular respiration, glycolysis, and metabolic flexibility in circulating cells. Evidence from cattle, swine, and poultry suggests that circulating cell bioenergetics reflects both immune function and whole-body metabolic competence. We propose that this approach holds promise as a diagnostic and research tool to monitor physiological stress, support early intervention, and generate insights into breeding or nutritional strategies in food-producing animals. Finally, we identify key methodological and translational gaps that must be addressed to realize the full potential of this approach in animal production systems.